Production of grease from used lubricant : a feasibility study - Nabil Fikri, Yaakub (2008)
Grease is a mixture of a fluid lubricant usually petroleum oil and a thickener soap) dispersed in the oil. The base oil (petroleum) can be changed by using the used lubricant. Other then base oil, thickener may play an important role in the mixture. Soap thickeners are formed by reacting metallic hydroxide, or alkali, with a fat, fatty acid, or ester. Since the petroleum prices were increase each year, using used lubricant as base oil is the best solution to produce grease in the low cost at the same time it will decrease the water pollution. Three type of soap are used in this production that is aluminum soap, calcium soap and sodium soap. Viscometer was use in this experiment to analyze the quality and performances of grease product to select the best type of soap to produce grease. The viscosities of grease are test by change the spindle speed for each type of soap. The different percent of soap are use to know the effect of percent of soap to the viscosity of grease. In this experiment, grease was successfully produced from used lubricant. The viscometer test and sample preparation on grease was visualized in this research, where the viscosity of grease was decrease with the increasing of spindle speed and the viscosity was increase with the increasing of percentage soap (thickener) added. The best way to produce grease is with sodium soap, where sodium soap is the strongest thickener compare to another thickener. Using this type of soap, only small amount of this thickener needed compare to another type of soap.